Medicinal plants in an urban environment: the medicinal flora of Banares Hindu University, Varanasi, Uttar Pradesh - Bussmann Rainer W; Kumar Munesh; Verma Archana K (BMC, 2007)
Abstract Varanasi is one of the oldest continuously inhabited cities of the world, and one of the most important Hindu pilgrimage sites. Despite this importance, very little information exits on the cities flora in general, and medicinal species found within its limit in particular. Traditional medicine plays a large role in Indian society. The presented study attempted to investigate if traditional plant use and availability of important common medicinal plants are maintained in urban environments. The paper presents information on the traditional uses of seventy-two plant species collected form the campus of Banares Hindu University, Varanasi, Uttar Pradesh, and highlights the uses of these plants by the local inhabitants.